The political economy of monetary institutions - Bernhard, William; Broz, J. Lawrence; Clark, William Roberts (Cambridge, Mass. : MIT Press, 2003)
This volume investigates the political economy of monetary institutions: central banks and exchange rate regimes.
"A special issue of International organization."
Includes bibliographical references.
osc 24/8/16
Loans
Keywords: Financial institutions; International organization; Banks and banking, Central; Monetary policy